Measurement of the ZZ production cross section and limits on anomalous neutral triple gauge couplings in proton-proton collisions at √s=7TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acerbi, E; et al. (2012)
A measurement of the ZZ production cross section in proton-proton collisions at √s=7TeV using data corresponding to an integrated luminosity of 1.02fb -1 recorded by the ATLAS experiment at the LHC is presented. Twelve events containing two Z boson candidates decaying to electrons and/or muons are observed, with an expected background of 0.3±0.3(stat)- 0.3+0.4(syst) events. The cross section measured in a phase-space region with good detector acceptance and for dilepton masses within the range 66 to 116 GeV is σZZ→" +" -" +" -fid=19.4-5.2+6.3(stat)-0.7+0. 9(syst)±0.7(lumi)fb. The resulting total cross section for on-shell ZZ production, σZZtot=8.5-2.3+2.7(stat)-0.3+0.4(syst)±0.3(lumi)pb, is consistent with the standard model expectation of 6.5-0.2+0.3pb calculated at the next-to-leading order in QCD. Limits on anomalous neutral triple gauge boson couplings are derived. © 2012 CERN. Published by the American Physical Society under the terms of the < uri xlink:href="http://creativecommons. org/licenses/by/3.0/" > Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.